Random size‐assortative mating despite size‐dependent fecundity in a Neotropical amphibian with explosive reproduction. (24th January 2018) - Székely, Diana; Székely, Paul; Denoël, Mathieu; Cogălniceanu, Dan
Abstract: Sexual selection theory predicts that, when body size is correlated with fecundity, there should be fitness advantages for mate choice of the largest females. Moreover, because larger males are expected to monopolise the largest females, this should result in an assortative mating based on body size. Although such patterns could be expected in both explosive and prolonged breeders, non‐assortative mating should be more widespread in species under time constraints. However, patterns of sexual selection are largely unexplored in explosive breeding species, and contrasting patterns have been found previously. We expect that the active choice of partners may be particularly risky when the time period during which sexual partners are available is severely limited. Therefore, to avoid missing an entire reproductive act, males and females should pair irrespective of traits, such as body size. We tested this hypothesis by investigating the mating patterns of the Pacific horned toad, Ceratophrys stolzmanni, a short‐lived fossorial species inhabiting Neotropical dry forests. This species is particularly adequate to test our prediction because it reproduces explosively over the course of a single night per year. Although the number of eggs laid was proportional to the size of females, and individuals of both sexes showed variation in body size, there was no assortative mating based either on size, body condition or age of mates. Egg size was not influenced by either female size or clutch size. The larger body size of females compared to males is likely due to fecundity selection, that is, the selective pressure that enhances reproductive output. Although we cannot dismiss the possibility that individuals could select their partners based on other criteria than those related to size or age, the results fit well our prediction, showing that the explosive breeding makes improbable an active choice of partners in both sexes and therefore favours a random mating pattern.